2017
DOI: 10.3390/ma11010059
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Corrosion Inhibitor for Mild Steel in Ethanol Fuel Blend

Abstract: The main aim of this study is to investigate Aganonerion polymorphum leaf-ethyl acetate extract (APL-EAE) and its inhibiting effect for steel in ethanol fuel blend. The immersion test, electrochemical and surface analysis techniques were successfully carried out in this research. Scanning electron microscope images indicated that the ethanol fuel blend induced pitting corrosion of steel. Remarkably, the surface of the sample containing 1000 ppm APL-EAE is smoother than the others submerged in different conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 28 publications
1
22
0
1
Order By: Relevance
“…When the APLE concentration reached 1000 ppm, the material density in the film became sufficient to minimize the number as well as the size of channels and pores, leading to a maximum protective effect. 11 However, the coating was thicker and the disorder in the structure increased when adding inhibitor concentrations beyond 1000 ppm, resulting in a sharp increase in the number of small size channels and pores that reduce protection. The protective mechanism of TNPs in a mixture with APLE indicated that the optimized size (10 nm) and concentration (30 ppm) of TNPs with the appropriate size (10 nm of diameter) and concentration (30 ppm) effectively filled the pores and channels in the APLE’s network to curb the penetration of corrosive agents from SEFB into the coating structure, thereby increasing the protective effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the APLE concentration reached 1000 ppm, the material density in the film became sufficient to minimize the number as well as the size of channels and pores, leading to a maximum protective effect. 11 However, the coating was thicker and the disorder in the structure increased when adding inhibitor concentrations beyond 1000 ppm, resulting in a sharp increase in the number of small size channels and pores that reduce protection. The protective mechanism of TNPs in a mixture with APLE indicated that the optimized size (10 nm) and concentration (30 ppm) of TNPs with the appropriate size (10 nm of diameter) and concentration (30 ppm) effectively filled the pores and channels in the APLE’s network to curb the penetration of corrosive agents from SEFB into the coating structure, thereby increasing the protective effect.…”
Section: Resultsmentioning
confidence: 99%
“…APLE was produced by the Soxhlet extraction process, the detailed process was presented in the previous report. 11 In short, fresh A. polymorphum leaves were dried at 60 °C, triturated to powder, and was added to a Soxhlet extractor containing ethyl acetate, and then extracted at 75 °C for 24 h. In the following step, the extract (APLE) was filtered, concentrated, and stored in a dry cabinet at room temperature. The extracted product was analyzed by an attenuated total reflectance Fourier transform infrared spectroscopy apparatus (α-FT-IR spectrometer), coupled with gas chromatography–mass spectroscopy (GC–MS) (Agilent 7890B for GC and Agilent 5977A for MS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Na(4-OHCin) and Ce(4-OHCin) 3 were synthesized as such that was previously reported [8]. Na(4-OHCin), CeCl 3 , and Ce(4-OHCin) 3 were dissolved in the simulated ethanol fuel blend contents are described previous work [6] and added slowly with stirring at 900 rpm and 38 ºC for 12 h making the final concentrations of 1800, 600, and 600 ppm of Na(4-OHCin), CeCl 3 , and Ce(4-OHCin) 3 , respectively. The steel coupons of 1.0 × 1.0 × 0.3 cm 3 used as working electrodes for the electrochemical tests were fabricated from steel sheet.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it leads an important study for new, more efficient, and environmentally benign inhibitor systems during the storage of gasoline. In the present decades, leaf extracts were a good recommendation for inhibiting corrosion with high performance [6]. However, these complexes molecular could effect to the products and its refined processes pay for the high energy and cost.…”
Section: Introductionmentioning
confidence: 99%